Peningkatan Kemampuan Berpikir Kritis Peserta Didik Melalui Model Pembelajaran Berbasis Isu-Isu Sosiosaintifik Ekologi - Rizka Ikhtianti Putri; Yanti Herlanti; Evi Muliyah (Universitas Sebelas Maret, 2025)
Critical thinking skills are an important component of 21st century skills, but students' skills in Indonesia are still low. This study aims to improve students' critical thinking skills through a socio-scientific issues-based learning model. The study used a quasi-experimental method with a non-equivalent pretest-posttest control group design involving students in class X.9 as the control class and students in class X.10 as the experimental class at SMA 5 Depok. The results showed that the socio-scientific issues learning model showed an increase in students' critical thinking skills with a significance value of 0.09. The average pretest score of the experimental class was 63.05, and after being treated, the average posttest score increased to 67.26. The standard deviation for the pretest was 12.46, while for the posttest it was 16.04. When compared to the PBL/PJbL learning model that teachers usually use for ecological concepts, critical thinking skills showed a significance value of -0.12. This significance value indicates that the two classes are not significantly different in critical thinking skills.